1990
DOI: 10.2105/ajph.80.suppl.47
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cigarette smoking among Hispanics in the United States: results from HHANES 1982-84.

Abstract: In the 1982-84 Hispanic Health and Nutrition Examination Survey, the prevalence of cigarette smoking was examined among Mexican Americans, Puerto Ricans, and Cuban Americans in the United States. Among 20-74 years olds, the age-adjusted smoking rates for Mexican American, Puerto Rican, and Cuban American men were high-42.5, 39.8, and 41.6 percent, respectively. Quite striking among Cuban American men was the high smoking rate among 20-34 year olds (50.1 percent), the highest smoking rate in the three Hispanic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1

Year Published

1992
1992
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 24 publications
3
71
1
Order By: Relevance
“…Second, these data may not be generalizable to Latinos from other national backgrounds, specifically Puerto Ricans and Cubans who are heavier smokers. 5 The fact that we adjusted for number of cigarettes smoked per day and found ethnic-specific differences would support a Latino cultural theme independent of national background. Third, several of the responses to smoking antecedents and reasons to quit smoking questions may be related to independent variables that remained unadjusted and could be addressed in future studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Second, these data may not be generalizable to Latinos from other national backgrounds, specifically Puerto Ricans and Cubans who are heavier smokers. 5 The fact that we adjusted for number of cigarettes smoked per day and found ethnic-specific differences would support a Latino cultural theme independent of national background. Third, several of the responses to smoking antecedents and reasons to quit smoking questions may be related to independent variables that remained unadjusted and could be addressed in future studies.…”
Section: Discussionmentioning
confidence: 89%
“…[5][6][7][8] Our previous work with convenience samples showed that compared with whites, Latinos are less likely to smoke in response to habitual cues, as likely to smoke in response to emotional cues, and more likely to want to quit because of cigarette smoke's effects on others' health, interpersonal relationships, and their own health. [9][10][11][12][13][14] Whether these differences in attitudes, beliefs, and behavior are related to ethnicity or are confounded by differences in education and level of nicotine dependence remains unclear.…”
Section: Settingmentioning
confidence: 99%
“…A variety of factors have been invoked by other authors, including the "healthy migrant" effect, a diet that includes more fruits and vegetables than the typical American diet, and protective psychosocial effects.26'27 However, survey data have shown that many risk factors are not more favorably distributed in US Hispanics, [28][29][30][31][32][33] and Hispanics have more limited access to health care than do Whites.434 It should be recognized, however, that cross-sectional surveys cannot characterize lifetime risk, and important secular trends may be occurring. As demonstrated by the data in this report, the age interaction suggests that conditions affecting younger adult men, notably extemal causes, are not less frequent in Hispanics, and conditions with a long latency, particularly cancer, probably play the predominant role in older individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Puerto Rican women (30.3%) also have higher age-adjusted smoking rates than Mexican American (23.8%) and Cuban (24.4%) women (48).…”
Section: Risk Behaviorsmentioning
confidence: 96%